2012
DOI: 10.1007/s11655-012-1116-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of traditional chinese medicine on acute myocardial infarction—A prospective cohort study

Abstract: CM therapy could decrease CM syndrome scores and blood-stasis syndrome score, reduce the rehospitalization rate during 6-month follow-up due to angina. Heart dysfunction and diabetes mellitus were hazard factors to end-point, whereas CM, PCI and ACE inhibitors were protective factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The rise in use may reflect even more government investment in preserving TCM, including more research on the effectiveness of TCM as well as broad insurance coverage for intravenous TCMs, which may influence the public’s perceptions about the benefits and safety of TCM. 14 Several recent studies published in the Chinese literature and in complementary medicine journals show improved biological and clinical outcomes, including improved angiographic coronary blood flow and reflow, 21 , 22 decreased stent restenosis, shorter hospital stays, less angina, 23 fewer readmissions, 23 improved quality of life, and improved short- and long-term mortality. 5 , 24 In the case of Salvia miltiorrhiza/danshen, the most widely used TCM, there are reports of superior efficacy and fewer side effects than nitroglycerin for the treatment of angina.…”
Section: Discussionmentioning
confidence: 99%
“…The rise in use may reflect even more government investment in preserving TCM, including more research on the effectiveness of TCM as well as broad insurance coverage for intravenous TCMs, which may influence the public’s perceptions about the benefits and safety of TCM. 14 Several recent studies published in the Chinese literature and in complementary medicine journals show improved biological and clinical outcomes, including improved angiographic coronary blood flow and reflow, 21 , 22 decreased stent restenosis, shorter hospital stays, less angina, 23 fewer readmissions, 23 improved quality of life, and improved short- and long-term mortality. 5 , 24 In the case of Salvia miltiorrhiza/danshen, the most widely used TCM, there are reports of superior efficacy and fewer side effects than nitroglycerin for the treatment of angina.…”
Section: Discussionmentioning
confidence: 99%
“…Although the morbidity and mortality of MI have been controlled to a large extent with early and effective preventive measures and interventions, there are still some problems in secondary prevention and rehabilitation of patients with MI. Chinese medicine (CM) shows some advantages in these aspects, such as improving the quality of life (QOL) and decreasing the rate of adverse events (Xu-Feng et al, 2010; Duan et al, 2012; Zhang Y.H., 2014). Several clinical studies with breviscapine have reported its effects on MI.…”
Section: Breviscapine For the Treatment Of Clinical Cvdsmentioning
confidence: 99%
“…But evidence from other research suggested that because of the long-term therapeutic effect of TCM, the number of readmissions and total expenses of treatment reduced with the participant of Chinese medical treatment [ 22 ]. For example, in the TCM treatment of acute myocardial infarction, the readmission rate due to angina during the 6-month follow-up in the treatment group (2.96%) was significantly lower than that in the control group (7.88%) [ 23 ]. Therefore, TCM dominant diseases are ubiquitous and need us to excavate through research.…”
Section: Discussionmentioning
confidence: 99%